Gaps in Spatial Planning of Water Resources Management for Metropolitan Areas: A Case Study of Chennai Metropolitan Area (CMA) - Sudha, M. Chaithanya; Ravichandran, S.; Ahmed, Sultan; Alam, Sarfaraz (National Geographical Journal of India, 2022)
Urban wetlands such as ponds, lakes, canals, rivers are souls of an urban ecosystem. The explosive growth of urban population and consequent spatial expansion of human settlements have brought about fundamental changes to the physical landscape of urban environment and to the people's perception of land, water and other elements of an urban environment. The decline in the geographical size, physical, chemical and biotic properties of water bodies has affected urban ecosystems, biodiversity, aesthetics of the landscape and also household economies. The process of degradation of water bodies and its adverse effect on local communities is particularly visible in peri-urban belts where significant numbers of people are still engaged in water-dependent economic occupations. The present paper provides the gaps in spatial planning where water resources management has not been addressed properly for the metropolitan areas of Chennai city. The study was conducted on the water bodies of Tambaram taluk. Six water bodies of Tambaram taluk that are located in the urban-rural gradient have been studied in detail. The study design includes the collection and analysis of primary and secondary data. To identify the land use changes during the urbanization process, satellite imageries were used to classify the land use patterns during a span of three decades. Three sets of imageries acquired from 1987 to 2009 from Institute of Water Studies, Taramani (Chennai) were used in the analysis. The study suggests that the area allocated for residential and institutional spaces by Metropolitan Development Authority increased by 23.27% from 1971 to 2009, while areas allocated for water bodies has been almost negligible. The result shows that the area under water in the Urban Velachery Lake has reduced drastically by 80.5% followed by peri-urban lakes Rajakeelpakkam (69.8 %) and Pallikaranai (39.9%). In view of these facts, the study suggests that the water sector planning should precede the master planning process of any urban agglomeration